Students' levels of awareness to computers and computer applications implication for the improvement of the University of the Philippines Los Baños (UPLB) Library Computerization Program - Pamulaklakin, Zenaida D. C. (1989)
This study seeks to examine the students' levels of awareness to computers and computer applications. Further, it seeks to examine the computer services available at the University of the Philippines Los Banos Main Library with the end view of making recommendations for the improvement of the library's computerization program.